SOLVING SOME NON-STANDARD PROBLEMS ABOUT TRIANGLES (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Solving of Planimetric problems of different forms and methods are presented in the article.